Regional Government Strategies in the Development of Sumenep Keraton Tourism in the Perspective Collaborative Governance - Istayu Pratistaning Utami; Khrisno Hadi; Yana Syafrieyana (Universitas Muhammadiyah Malang, 2019)
Sumenep Regency has high tourism potential where there are about 32 tourist attractions in which one of them is Sumenep Palace. However, in 2016 Sumenep Palace is still less touristy compared to other tourist attractions such as Lombang Beach which can attract around 66.000 tourists, while Sumenep Palace is only around 49.000. In addition, some travel agents also still do little tourism promotion, because they prefer to offer beach tour packages. Therefore, in order for tourism development to run optimally, Sumenep Regency carries out a collaborative strategy involving the private sector and the community. The research method used was the descriptive qualitative method to provide an overview of the strategy of Sumenep Regency Government in developing tourism of Sumenep Palace based on collaborative strategy. Data collection techniques are carried out through the process of observation, interviews, and documentation. The theory used is collaborative governance by Chriss Ansell and Alisson Gash which emphasizes that collaboration is carried out formally between government and non-government actors, where the government becomes the initiator in the collaboration. The results showed that the collaboration included government actors carried out by Disparbudpora, travel tourism agents and klenengan art groups. Each of these actors has acted as a facilitator, carried out tourism promotions, and supported the implementation of collaboration activities. The achievements of collaborative activities indicate the presence of increasing tourist visits from 2016 to 2017, but in terms of regional revenue, the contribution is still not that significant. Overall, the realization of the collaboration is supported by a forum for dialogue, trust, and commitment between actors. But there are some drawbacks in the absence of regulations to support the collaboration process, the absence of hotel and restaurant involvement and the lack of involvement of travel agents.Key Word: Government Strategy, Collaborative Governance, Tourism Development